2020
DOI: 10.21203/rs.3.rs-50750/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enzymatic activities and analysis of a mycelium-based composite formation using peach palm (Bactris gasipaes) residues on Lentinula edodes

Abstract: By seeding fungus on top of industry residues, a mycelium can grow and form a compact network structure; however, it may not develop due to lack of optimal nutrients from the substrate. Consequently, peach palm residues can be a potential alternative; so, to test this hypothesis, this work evaluates the effect of peach palm residues as substrate for the growth of mycelium based on Lentinula edodes . They were also supplemented with cassava bran and various sources of nitrogen – ammonium sulphate, potassium nit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Several research studies have concluded that MBCs can be defined as hydroscopic materials, while the water absorption ability of MBCs was influenced by the type of substrate and fungal species. This characteristic is usually associated with a cellulose component (a large number of accessible hydroxyl groups) and hydrophilic mycelium [19,21,28,29,32,36,42,[95][96][97]. Therefore, the differences in the water absorption abilities of various MBCs were found to be related to differences in the chemical components of the composites.…”
Section: Water Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several research studies have concluded that MBCs can be defined as hydroscopic materials, while the water absorption ability of MBCs was influenced by the type of substrate and fungal species. This characteristic is usually associated with a cellulose component (a large number of accessible hydroxyl groups) and hydrophilic mycelium [19,21,28,29,32,36,42,[95][96][97]. Therefore, the differences in the water absorption abilities of various MBCs were found to be related to differences in the chemical components of the composites.…”
Section: Water Absorptionmentioning
confidence: 99%
“…Furthermore, mycelium-based construction materials derived from MBCs have been developed on a laboratory scale in several cumulative forms, including block materials, particle board, acoustic materials, thermal insulation, cladding materials, surface materials (thin sheets and film), and paste materials [19,[26][27][28][29][30][31]. MBCs are generated from various forms of lignocellulosic residues and fungal species that are available in each country [27,32]. However, different species of fungi and different substrate types can directly affect the properties of the final products and the functional aspects of the resulting MBCs [23,24,27,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation